Tuberculous Peritonitis Presenting Acute Recurrent Pancreatitis - Birry Karim; Afifah Is; Ikhwan Rinaldi; Ari Fahrial Syam; Murdani Abdullah; Ceva Wicaksono Pitoyo (The Indonesian Society for Digestive Endoscopy, 2009)
Tuberculosis (TB), one of the oldest diseases known to affect humans, is a major cause of death worldwide. TB is still a major problem in Indonesia. This disease, which is caused by bacteria of the Mycobacterium tuberculosis, usually affects the lungs, although other organs are involved in up to one- third of cases. Approximately 95% cases of TB and 98% death because of TB occur in developing country. Gastrointestinal tuberculosis is uncommon, making up 3.5% of extrapulmonary cases in the United States. This kind of TB may involve gastrointestinal tract, peritoneal, lymph nodes, or solid intraabdominal organs (viscera). A 17 years old male admitted to hospital with TB peritonitis presenting unusual clinical manifestation. At the first admission patients was diagnosed with acute pancreatitis based on elevation of amylase and lipase level up to 285 and 2,046 U/L and after finishing further examination, patients suffered from tuberculous peritonitis which based on literature manifested some gastrointestinal disorders. Diagnostic confirmation was accomplished by conducting serum-ascites albumin gradient (SAAG) of 1.1 g/dL, peritoneal thickening and the presence of ascites with fine mobile septations on ultrasound, positive polymerase chain reaction (PCR) TB from ascitic fluid. Patients received conventional antitubercular therapy for 12 months of rifampicin, isoniazid, pyrazinamide, and ethambutol. The addition of corticosteroids for the first two or three months of treatment may reduce the incidence of late complications arising from adhesive disease, such as small bowel obstruction. Keywords: mycobacterium tuberculosis, tuberculous peritonitis, PCR, serum-ascites albumin gradient